(3QSGdI TYQ GdfaSs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3Edi ZGjI GdZGjGJ bUOi hfYJi Edi GdMGce GdYGdi Ydi cd MGce Edi GdMGce GdefUhQ adjS ai GdJhMjO ajg HfGOe s
(3BNQgG (B:s
(3SjcXe gPG GdTYQ cd efGab hjROGO cXekG ahb cXe GdCcGXe hGdSdGe HMeO ehdGfG hefg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B41s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds